Penyusunan Laporan Keuangan Yayasan Pondok Pesantren Nurul Ibad Jakarta Timur Berdasarkan ISAK 335 dengan Program Akoontan.com - Putri, Septyana; Handarini, Dwi; Sasmi, Aji Ahmadi (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
In the digital era, technology is transforming various aspects of life, including accounting regulations. Applications like Akoontan.com facilitate transaction recording and financial report preparation in compliance with ISAK 335 for non-profit organizations. This study explores the implementation of Akoontan.com at Nurul Ibad, East Jakarta Islamic Boarding School, using a Research and Development (R&D) design with the ADDIE model. Data was collected through interviews and foundation documents. The results indicate that the use of Akoontan.com simplifies the preparation of financial reports, enhancing transparency, accountability, and operational efficiency. The study recommends more in-depth data collection and a longer research period, as well as the development of a more effective and efficient financial report preparation module for the foundation in accordance with ISAK 335 using Akoontan.com.